1980
DOI: 10.1136/jcp.33.1.72
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the Mi-Mark endoemtrial sampling technique.

Abstract: SUMMARY One hundred and twenty cytological smears and 106 histological specimens were obtained from 115 patients using a new technique of endometrial sampling. It proved an atraumatic procedure and was well accepted by the patients. Some problems were encountered in the preparation of satisfactory cytological specimens and in their interpretation. The method was not completely reliable for detecting endometrial pathology and is therefore considered unsuitable for monitoring patients on hormone replacement ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…One of the aims of the endometrial cytology is to detect early endometrial cancer and to differentiate this pathologic entity from endometrial hyperplasia. The cytologic features of endometrial hyperplasia in endometrial aspirates have been described by Morse, but other groups report that the lesions are underdiagnosed . The diagnostic criteria that reflected the cytoarchitecture (architecture of cell clumps) in endometrial cytology has been reported to solve those problems .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the aims of the endometrial cytology is to detect early endometrial cancer and to differentiate this pathologic entity from endometrial hyperplasia. The cytologic features of endometrial hyperplasia in endometrial aspirates have been described by Morse, but other groups report that the lesions are underdiagnosed . The diagnostic criteria that reflected the cytoarchitecture (architecture of cell clumps) in endometrial cytology has been reported to solve those problems .…”
mentioning
confidence: 99%
“…The cytologic features of endometrial hyperplasia in endometrial aspirates have been described by Morse,7 but other groups report that the lesions are underdiagnosed. 8,9 The diagnostic criteria that reflected the cytoarchitecture (architecture of cell clumps) in endometrial cytology has been reported to solve those problems. [10][11][12] However, overlapping cytomorphologic features (dilated or branched pattern, irregular protrusion) between endometrial hyperplasia (with and without atypia) and low-grade endometrioid endometrial carcinoma (LG-ENEC), may still cause diagnostic problems.…”
mentioning
confidence: 99%
“…8 A wide variety of appliances have been used for endometrial aspiration by various authors like intrauterine aspiration cannula, isaacs endometrial cell sampler, vabra aspirator, uterobrush, endocyte, pipelle, karman's cannula, etc. 9 The amount of material obtained, the appearance of cells and their distribution largely depend on the technique used for collection, processing, and staining. In our study, 100 patients with dysfunctional uterine bleeding were subjected to endometrial aspiration using a 3mm diameter plastic disposable pipeline.…”
Section: Discussionmentioning
confidence: 99%